Water Quality of Vishav Stream in Kashmir Valley, J & K, India - Ashok K. Pandit, Assadullah Sheikh, Amit Pal (Recent Research in Science and Technology, 2010)
Present study has been carried out at Vishav stream, which is one of the most live and perennial tributaries of River Jhelum of Kashmir valley. Vishav contributes major portion of discharge towards the Jhelum. Due to increase the population and over exploitation of fresh water resources and waste water disposal, the direct or indirect modifications and alterations in creating the physical, chemical and biological characteristics of water have occurred profound and deleterious effects on human health and on the environment as a whole. In present investigation an attempt was made to find out the physico-chemical nature of Vishav stream, so as to have an insight into the level of pollution status in the stream. In order to have reasonable and wholesome information, a detail study of the stream course was conducted on monthly basis and the selection of sites was done keeping in mind different types of habitat features i.e., elevations, fast flowing areas, slow zones, as well as human interferences. Study showed that the deterioration of stream water quality at lower reaches as low transparency, DO and higher concentration of Ca, N, P, Cl etc. all pointing towards the nutrient enrichment.